The Relationship of Anxiety Level with Sugar Levels Blood in People with Diabetes Mellitus Type 2 at Technical Implementation Unit of Melak Public Health Center - Taufik Oktavianur (Jurnal KESANS : Kesehatan dan Sains, 2023)
Introduction: Indonesia is ranked 7th in the world with 10.7 million people with diabetes. If this disease is not controlled properly, it will result in an increase in blood glucose levels (hyperglycemia) which can cause various complications, namely metabolic complications, microvascular complications, neuropathy complications and macrovascular complications. Objective: To determine the relationship between anxiety levels and blood sugar levels in patients with Type 2 Diabetes Mellitus at Technical Implementation Unit of Melak Public Health Center.  Methods: The research design in this study was descriptive correlation using a cross-sectional approach. Determination of the sample using purposive sampling, with a sample of 56 respondents. Result and Discussion: The level of anxiety in the Technical Implementation Unit of Melak Public Health Center is in the high category (51.8%). Fasting blood sugar levels at Technical Implementation Unit of Melak Public Health Center in the high category (57.1%). The relationship between anxiety levels and blood sugar levels obtained p-value = 0.01 smaller than 0.05 then Ha is accepted and H0 is rejected, meaning that there is a relationship between anxiety levels and blood sugar levels in patients with Type 2 Diabetes Mellitus.  Conclusion: There is a relationship between anxiety levels and blood sugar levels in patients with Type 2 Diabetes Mellitus at Technical Implementation Unit of Melak Public Health Center.